2016
DOI: 10.1186/s12957-016-0831-7
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma on cirrhosis complicated with tumoral thrombi extended to the right atrium: results in three cases treated with major hepatectomy and thrombectomy under hypothermic cardiocirculatory arrest and literature review

Abstract: BackgroundHepatocellular carcinoma (HCC) with the presence of tumor thrombus in hepatic veins and vena cava, until the atrium (RATT), is correlated with poor prognosis and with risk of tricuspid valve occlusion, congestive heart failure, and pulmonary embolism.MethodsThree patients with HCC on cirrhotic liver with RATT were studied. Operative technique, pre-operative and post-operative liver function tests, blood loss and transfusions, post-operative morbidity and mortality, and the overall survival and the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 25 publications
(37 reference statements)
0
21
0
Order By: Relevance
“…If HCC with a tumor thrombus in the IVC and RA is found during the end stage, the prognosis is very poor. If not treated, the survival time is between three days and two months . Our patient survived only 43 days after admission.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…If HCC with a tumor thrombus in the IVC and RA is found during the end stage, the prognosis is very poor. If not treated, the survival time is between three days and two months . Our patient survived only 43 days after admission.…”
Section: Discussionmentioning
confidence: 78%
“…Hepatocellular carcinoma is the third most common cause of cancer‐related death worldwide . HCC often causes portal vein tumor thrombus formation, with metastasis to the liver, lungs, and other organs, while direct invasion of the hepatic vein and formation of a tumor thrombus extending into the IVC and RA is relatively rare.…”
Section: Introductionmentioning
confidence: 99%
“…However, higher values of indocyanine green clearance are not an absolute surgical contraindication as for the possible clearance impairment by tumor-related vascular obstruction [57]. Pesi et al [35] summarized that RA tumor thrombus removal could be performed in three ways: 1) with the use of THVE of the liver without CPB, which is indicated for tumor thrombi with an initial contiguity to the RA; 2) normothermic CPB with THVE; and 3) CPB with hypothermic circulatory arrest, but its use is limited due to potentially intraoperative bleeding, possible brain damage and postoperative liver dysfunction. Wang et al [3] reported that they performed cavoatrial thrombectomy for HCC patients with RA thrombus by modifying procedures as minimally invasive as possible depending on the extension of the tumor thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…The timing of diagnosis of RA thrombi was described for 53 patients: at HCC recurrence in 5 (9.4%) patients [1,5,13,15,30], at HCC progression in 13 (24.5%) patients [1, 17, 19, 34, 36-38, 40, 42, 48, 51], and at the first HCC diagnosis in 35 The size of liver tumor was described for 57 patients. The calculated tumor size was 8.4±4.1 (range, 1.3-21; median, 7.6) cm, with only 3 (5.3%) tumors of 3 patients <3 cm [1,6,51].…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Type III describes thrombi that reach to the right atrium and require hemihepatectomy and thrombectomy with cardiopulmonary bypass [22]. There are many case reports indicating a beneficial outcome and long survival periods of up to 15 months for patients who underwent curative resection [23]. However, to be suitable for surgical treatment, particularly with cardiopulmonary bypass, patients with HCC have to be in a good general health without severe comorbidities [16].…”
Section: Discussionmentioning
confidence: 99%